Chemogenetic manipulation of parasympathetic neurons (DMV) regulates feeding behavior and energy metabolism. (1st November 2019) - NamKoong, Cherl; Song, Woo Jin; Kim, Chang Yeon; Chun, Duck Hyeon; Shin, Soonho; Sohn, Jong-Woo; Choi, Hyung Jin
Highlights: Activation of parasympathetic neuron by intraperitoneal injection of the clozapine-N-oxide (CNO) suppressed food intake and body weight loss. Parasympathetic neurons activation in improved glucose tolerance while inhibition of the neurons resulted in impaired glucose tolerance. Stimulation of the parasympathetic nervous system by injection of CNO increased oxygen consumption and energy expenditure. Abstract: Parasympathetic nervous system (PNS) innervates with several peripheral organs such as liver, pancreas and regulates energy metabolism. However, the direct role of PNS on food intake has been poorly understood. In the present study, we investigated the role of parasympathetic nervous system in regulation of feeding by chemogenetic methods. Adeno associated virus carrying DREADD (designer receptors exclusively activated by designer drugs) infused into the target brain region by stereotaxic surgery. The stimulatory hM3Dq or inhibitory hM4Di DREADD was over-expressed in selective population of dorsal motor nucleus of the vagus (DMV) neurons by Cre-recombinase-dependent manners. Activation of parasympathetic neuron by intraperitoneal injection of the M3-muscarinic receptor ligand clozapine -N-o xide (CNO) (1 mg/kg) suppressed food intake and resulted in body weight loss in ChAT-Cre mice. Parasympathetic neurons activation resulted in improved glucose tolerance while inhibition of the neurons resulted in impaired glucose tolerance. Stimulation of parasympathetic nervous system by injection of CNO (1 mg/kg) increased oxygen consumption and energy expenditure. Within the hypothalamus, in the arcuate nucleus (ARC) changed AGRP/POMC neurons. These results suggest that direct activation of parasympathetic nervous system decreases food intake and body weight with improved glucose tolerance.